Apoptosis and inflammation - C. Haanen; I. Vermes (Hindawi Limited, 1995)
During the last few decades it has been recognized that cell death is not the consequence of accidental injury, but is the expression of a cell suicide programme. Kerr et al. (1972) introduced the term apoptosis. This form of cell death is under the influence of hormones, growth factors and cytokines, which depending upon the receptors present on the target cells, may activate a genetically controlled cell elimination process. During apoptosis the cell membrane remains intact and the cell breaks into apoptotic bodies, which are phagocytosed. Apoptosis, in contrast to necrosis, is not harmful to the host and does not induce any inflammatory reaction. The principal event that leads to inflammatory disease is cell damage, induced by chemical/physical injury, anoxia or starvation. Cell damage means leakage of cell contents into the adjacent tissues, resulting in the capillary transmigration of granulocytes to the injured tissue. The accumulation of neutrophils and release of enzymes and oxygen radicals enhances the inflammatory reaction. Until now there has been little research into the factors controlling the accumulation and the tissue load of granulocytes and their histotoxic products in inflammatory processes. Neutrophil apoptosis may represent an important event in the control of intlamtnation. It has been assumed that granulocytes disintegrate to apoptotic bodies before their fragments are removed by local macrophages. Removal of neutrophils from the inflammatory site without release of granule contents is of paramount importance for cessation of inflammation. In conclusion, apoptotic cell death plays an important role in inflammatory processes and in the resolution of inflammatory reactions. The facts known at present should stimulate further research into the role of neutrophil, eosinophil and macrophage apoptosis in inflammatory diseases.